Heat-health vulnerability in temperate climates: lessons and response options from Ireland - Shona K. Paterson; Christie Nicole Godsmark (BMC, 2020)
Abstract Background In Ireland, rising temperatures remains the climate projection that national climate scientists associate with the highest degree of confidence. However, the health challenge of heat has been largely absent from Ireland's public health sector. This is epitomised by the lack of a comprehensive public health-focused heat-health action plan or country-specific codes of practice for heat-health when working outdoors. Our objective is to highlight the anticipated heat-health challenges in Ireland, and other temperate regions, through analysing vulnerable groups and systems, reinforcing the need to respond. Methods A scoping literature review was conducted to determine how heat affects health of the vulnerable in temperate climatic regions, with a focus on Ireland. Additionally, national Google Trends data was coarsely analysed to determine whether heat is a growing societal concern. Results and discussion The heat-vulnerable include: older people; chronically ill; infants, pregnant women, children; outdoor workers; socio-economically disadvantaged; urban dwellers; food systems and the health sector. Google Trends data suggest an increase in heat-related health searches over time, demonstrating rising levels of concern to temperature increases, reinforcing a gap in national policy associated with communication of, and response to, the heat-health challenge. Specific, actionable recommendations for adaptation and mitigation strategies are proposed. Conclusion Heat poses a public and occupational health challenge, receiving limited attention in Ireland. Lack of a co-ordinated effort, places vulnerable populations at risk. Our recommendations, with reference to vulnerable groups and acknowledging the multi-sectoral nature of heat-health and climate change, advocate for the adoption of a "health and climate change in all policies" approach and the development of a public health-focused heat-health action plan.